Functionalization of ethylene vinyl acetate with antimicrobial chlorhexidine hexametaphosphate nanoparticles - Wood NJ (Dove Medical Press, 2014)
Natalie J Wood,1–3 Sarah E Maddocks,4 Helena J Grady,1,2 Andrew M Collins,2 Michele E Barbour11Oral Nanoscience, School of Oral and Dental Sciences, 2Bristol Centre for Functional Nanomaterials, 3Centre for Organised Matter Chemistry, School of Chemistry, University of Bristol, UK; 4School of Health Sciences, Cardiff Metropolitan University, UKAbstract: Ethylene vinyl acetate (EVA) is in widespread use as a polymeric biomaterial with diverse applications such as intravitreal devices, catheters, artificial organs, and mouthguards. Many biomaterials are inherently prone to bacterial colonization, as the human body is host to a vast array of microbes. This can lead to infection at the biomaterial’s site of implantation or application. In this study, EVA was coated with chlorhexidine (CHX) hexametaphosphate (HMP) nanoparticles (NPs) precipitated using two different reagent concentrations: CHX-HMP-5 (5 mM CHX and HMP) and CHX-HMP-0.5 (0.5 mM CHX and HMP). Data gathered using dynamic light scattering, transmission electron microscopy, and atomic force microscopy indicated that the NPs were polydisperse, ~40–80 nm in diameter, and aggregated in solution to form clusters of ~140–200 nm and some much larger aggregates of 4–5 µM. CHX-HMP-5 formed large deposits on the polymer surface discernible using scanning electron microscopy, whereas CHX-HMP-0.5 did not. Soluble CHX was released by CHX-HMP-5 NP-coated surfaces over the experimental period of 56 days. CHX-HMP-5 NPs prevented growth of methicillin-resistant Staphylococcus aureus when applied to the polymer surfaces, and also inhibited or prevented growth of Pseudomonas aeruginosa with greater efficacy when the NP suspension was not rinsed from the polymer surface, providing a greater NP coverage. This approach may provide a useful means to treat medical devices fabricated from EVA to render them resistant to colonization by pathogenic microorganisms.Keywords: EVA, biomaterial, polymer